Phosphorylation of p53 Serine 15 Is a Predictor of Survival for Patients with Hepatocellular Carcinoma - Taewoo Yang; Yegyun Choi; Jae Won Joh; Steve K. Cho; Dae-Shick Kim; Sung-Gyoo Park (Canadian Journal of Gastroenterology and Hepatology)
Background. Hepatocellular carcinoma (HCC) is one of the most common malignant cancers with a poor prognosis. Several commonly investigated immunohistochemical markers in resected HCC have potential prognostic value, but the prognostic utility of p53 expression in HCC has remained elusive. Aim. To evaluate the prognostic value of p53 and p53 phosphorylation at serine 15 (p53 Ser15-P) in patients with HCC. Methods. Surgically resected tumors from 199 HCC patients were analyzed for p21, p53, p53 Ser15-P, and proliferating cell nuclear antigen (PCNA) expression using immunohistochemistry. Results. Stratifying by the expression of p53 Ser15-P (P = 0.016), but not by p53 (P = 0.301), revealed significantly different survival outcomes in patients with HCC. Moreover, our analysis demonstrated that patients who were PCNA-positive and p53 Ser15-P–negative had significantly worse survival outcomes (P = 0.001) than patients who were PCNA-positive and p53 Ser15-P–positive. Conclusions. P53 Ser15-P is associated with poor outcomes in patients with HCC, and this prognostic marker is useful for predicting the survival of patients with PCNA-positive HCC.